Desain dan Uji Coba Video Pembelajaran Dengan Bantuan Software Wondershare Filmora pada Materi Asam Basa - rizqi ridhona; Arif Yasthophi (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
This research was instigated by the lack of student interest in reading books, so it was needed amedia such a tutorial video that could help students understand the lesson. This research aimed atdesigning a valid tutorial video with Wondershare Filmora software on Acid Base lesson based onvalidation by the experts of material and media, and the practicality test by teachers and students.It was Research and Development (R&D) with Borg and Gall development model. The steps in thisresearch were 1) researching and collecting information, 2) planning, 3) developing the initialform of the product, and 4) preliminary field testing, 5) revising the product. Preliminary fieldtesting was conducted at the tenth-grade students of Natural Science Ikhwan of Islamic IntegratedSenior High School of Al-Fityah Pekanbaru. The validation result by the experts of media andmaterial was 91.25% and it was on very valid criterion. The result of teacher practicality test was95.13%, and it was on very practical category. The result of student practicality test was 82.7%,and it was on very practical category.